Optimization of microwave-assisted hydrolysis of glucose from oil palm empty fruit bunch - Maya Sarah; Isti Madinah; Erni Misran; Fatimah (South African Journal of Chemical Engineering)
Hydrolysis of oil palm empty fruit bunches (OPEFB) using microwave as an energy source is carried out to produce sugar with mild operating conditions. One way to find the best conditions that can obtain high-quality sugar is to optimize the hydrolysis process. In this study, optimization was carried out using Response Surface Methodology (RSM) with a Central Composite Design (CCD) experimental design. Estimated variables to affect the hydrolysis process are the ratio of OPEFB to solvent (X1: 1:20–4:20 g/ml), solvent concentration (X2: 0.5–1.5 %), and hydrolysis time (X3: 5–15 min). Hydrolysis success parameters were measured by hydrolysis temperature (Y1), glucose (Y2), fructose (Y3), and total sugar (Y4) concentration. The optimization results show that the three independent variables contribute 53.25 % to the hydrolysis temperature and 86.42 % to the sugar concentration. The recommended operating conditions were hydrolysis with the ratio of OPEFB to solvent of 4:20 g/ml, solvent concentration of 0.5 %, and carried out for 10 min. The hydrolysis temperature cannot be optimized because there is a mismatch in the temperature model analysis. The application of these conditions is predicted to produce glucose, fructose, and total sugar of 315.51; 258.24; 573.85 mg/L respectively. The last step is to validate these conditions in the laboratory to get the actual value. Actual glucose, fructose, and total sugar obtained were 300.40; 245.44; 545.84 mg/L respectively. The error in this study is less than 5 % which indicates the actual value is following the predicted value. © 2001 Elsevier Science. All rights reserved.